The Need Analysis of English for Specific Purposes for The Tenth Grade Computer Engineering and Networking Students at SMKN 3 Takalar - Nur Hamidah; Pidia Warahma; Al Qadri Halim; Ayu Lestari; Ryzka Ramasyari; Andini Agustiani (Politeknik Siber Cerdika Internasional, 2026)
This research examines the English language needs of tenth-grade Computer Engineering and Networking students at SMKN 3 Takalar, aiming to design an English for Specific Purposes (ESP) curriculum tailored to their academic and professional requirements. A questionnaire involving 60 students revealed that most are motivated to learn English for career preparation and global communication. Writing and speaking were identified as the most essential skills, though speaking posed the greatest challenge due to limited practice, lack of confidence, and minimal peer interaction. Students preferred interactive learning methods such as group discussions, presentation simulations, project-based learning, and multimedia use. They also favored digital resources like learning apps and videos. Major barriers included limited study time, insufficient speaking practice, and a lack of relevant resources. Thus, an effective ESP curriculum should integrate technology, encourage active learning, and adopt collaborative approaches aligned with students' needs. Additionally, incorporating real-world tasks can help bridge the gap between theoretical knowledge and practical application. This study underscores the importance of ESP in vocational education for enhancing English proficiency, critical thinking, collaboration, and problem-solving skills. With the right approach, ESP can serve as a transformative tool in preparing students to excel academically and professionally. The findings carry direct implications for curriculum developers, English teachers, and educational policymakers in Indonesian vocational schools, underscoring the need for context-sensitive, technology-enhanced ESP programs that bridge disciplinary demands with learner realities.